Mast fruiting is a frequent strategy in woody species of eastern South America. - Natalia Norden; Jérôme Chave; Pierre Belbenoit; Adeline Caubère; Patrick Châtelet; Pierre-Michel Forget; Christophe Thébaud (PLoS ONE, 2007)
BACKGROUND: It is thought that mast seeding is a rare reproductive strategy in the tropics, since tropical climates are less variable, and fruit consumers tend to be more generalist in these regions. However, previous tests of this hypothesis were based on only few tropical datasets, and none from tropical South America. Moreover, reproductive strategies have been quantified based on the coefficient of variation of interannual seed production, an index that potentially confounds masting and high interannual variability in seed production. METHODOLOGY/PRINCIPAL FINDINGS: We developed a new approach to model the monthly variability in seed production for 28 tree species, and 20 liana species monitored during 5 years in a tropical forest of Central French Guiana. We found that 23% of the species showed a masting pattern, 54% an annual fruiting pattern, and 23% an irregular fruiting pattern. The majority of masting species were trees (8 out of 11), most of them animal-dispersed. The classification into reproductive strategies based on the coefficient of variation was inconsistent with our results in nearly half of the cases. CONCLUSIONS/SIGNIFICANCE: Our study is the first to clearly evidence the frequency of the masting strategy in a tropical forest community of Eastern South America. The commonness of the masting strategy in tropical plants may promote species coexistence through storage dynamics.